The efficacy of clonidine on intraoperative bleeding in middle ear microsurgery - Arash Jafariye; Fatemeh Hajimohammadi; Afshar Etemadi Al-e-Agha; Azadeh Salavatipour; Mohsen Rajati Haghi (Iranian Journal of Otorhinolaryngology, 2010)
Introduction: The aim of this study was to evaluate the efficacy of clonidine on intraoperative bleeding in middle ear microsurgery. Materials and Methods: This prospective double-blinded clinical trial was performed on 51 patients (ASA I, II), aged 15-60 year undergoing middle ear microsurgery. They were randomly assigned to receive either 200 micrograms clonidine per oral or placebo 90 minutes prior the operation in a double blind condition. Intraoperative bleeding was assessed on a four-point scale. Systemic blood pressure and heart rate were measured before and during surgery. Intraoperative bleeding, antihypertensive requirements, cardiovascular changes after intubation, post operative bleeding and reoperations were compared between two groups.  Results: Clonidine group had a better bloodless surgical field than placebo group (P